Study on flow force compensation characteristics and optimization design of jet guiding groove. (August 2022) - Ding, Xinkai; Li, Ruichuan; Xu, Jikang; Liu, Qi; Cheng, Yi; Liu, Jilu
Abstract: A jet guiding groove is designed on the spool to compensate the steady-state flow force. The steady-state flow force model is analyzed and derived. The influence of structural parameters on steady-state flow force is studied by CFD simulation. The response surface method is used to construct the steady-state flow force polynomial regression model. The optimal structure size of the jet guiding groove is obtained. The steady-state flow force compensation coefficient is defined and calculated. Results show that the compensation effect decreases with the increase of pressure difference. However, at the same pressure difference, the absolute value of the compensation coefficient of the spool with jet guiding groove is less than that of the spool without jet guiding groove. The results show that the jet guiding groove can effectively compensate the steady-state flow force and improve the control accuracy of the valve. Highlights: Jet guiding groove can effectively compensate the flow force. The influence of structural parameters on steady-state flow force is studied by CFD simulation. The flow force model is established by response surface and the optimal parameters are calculated. The flow force compensation coefficient can be used to analyze the compensation characteristics.